2019
DOI: 10.1016/j.apsb.2019.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-tuned liposomal membrane rigidity directs tumor penetration and anti-tumor effect

Abstract: Recently, liposomes have been widely used in cancer therapeutics, but their anti-tumor effects are suboptimal due to limited tumor penetration. To solve this problem, researchers have made significant efforts to optimize liposomal diameters and potentials, but little attention has been paid to liposomal membrane rigidity. Herein, we sought to demonstrate the effects of cholesterol-tuned liposomal membrane rigidity on tumor penetration and anti-tumor effects. In this study, liposomes composed of hydrogenated so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 52 publications
2
40
0
Order By: Relevance
“…Lipid vesicles were composed of HSPC/CH/DSPE-PEG (3:1:1, w / w / w ). Cholesterol was used to reduce the rigidity of the lipid membrane and enhance the penetration of lipid vesicles 25 . All DOX-loaded lipid vesicles (lipids:DOX = 10:1, w / w ) were prepared using the lipid film hydration method.…”
Section: Methodsmentioning
confidence: 99%
“…Lipid vesicles were composed of HSPC/CH/DSPE-PEG (3:1:1, w / w / w ). Cholesterol was used to reduce the rigidity of the lipid membrane and enhance the penetration of lipid vesicles 25 . All DOX-loaded lipid vesicles (lipids:DOX = 10:1, w / w ) were prepared using the lipid film hydration method.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the literatures, we hypothesized that this may be related to differences in the composition and properties of cell membranes. [30][31][32] In addition, the specific integrin proteins of ACNVs may also determine cell tropism. 11,33,34 To further investigate the endocytosis mechanism of ACNVs, HepG2 cells were incubated with endocytosis inhibitors (chlorpromazine hydrochloride, amiloride, nystatin, and cytochalasin D).…”
Section: Cellular Uptake Assessmentmentioning
confidence: 99%
“…The authors reported a decrease in the membrane rigidity of the liposomes as the cholesterol content increased. The aforementioned findings suggest that when the liposomal membranes are less rigid, there is an increase in surface contact with the cells resulting in a prolonged cellular uptake [ 62 ].…”
Section: Application Of Cholesterol-based Carriers In Anticancer Dmentioning
confidence: 99%
“…Lip3 and Lip2 displayed moderate rigidity inhibiting tumor spheroid growth and exhibited high tumor penetration with excellent tumor growth inhibition in vivo. The results showed that moderate liposomal rigidity resulted in better diffusivity making cholesterol-tuned liposomes a promising system for delivery drugs to tumor cells [ 62 ].…”
Section: Application Of Cholesterol-based Carriers In Anticancer Dmentioning
confidence: 99%